A history of race in Muslim West Africa, 1600-1960 - Hall, Bruce S. (African studies ;, 2011)
This book traces the development of African arguments about race over a period of more than 350 years in the Niger Bend in northern Mali. Bruce S. Hall reconstructs an African intellectual history of race that long predated colonial conquest, and which has continued to orient community relations ever since.